HUBUNGAN TINGKAT DEPRESI DENGAN KUALITAS HIDUP PADA PENDERITA HIV/AIDS DI RUMAH SAKIT SANTA ELISABETH BATAM TAHUN 2018 - Ika Novita Sari; Reci Hamdayani; Lisastri Syahrias (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Human Immunodeficiency Virus-Aciqired Immuno Deficinc Syndrome (HIV-AIDS) is a global problem and is one of the public health problems in Indonesia. Researchers presurveyed at Santa Elisabet Batam Hospital on May 28, 2018 obtained data from medical records, the number of each month was HIV / AIDS patients who visited the hospital from January as many as 110 people, February as many as 121 people, March as many as 127 people, April as many as 122 people and in May 152 people. The amount from January to May 2018 is 632 people, from the data above that routinely visits 30 months. The purpose of this study was to find out the relationship between the level of depression and quality of life in people with HIV / AIDS at Santa Elisabeth Batam Hospital in 2018. The study design used an analytical survey method with a cross sectional approach. The population in this study were all patients suffering from HIV / AIDS who were treated at Santa Elisabeth Hospital in Batam. The sample technique uses purposive sampling with a total sample of 30 people. The study was conducted on June 26 to July 17 2018. Collecting data by questionnaire. Data analysis used is univariate and bivariate with Chi-Square test to see the relationship of two variables. The results obtained by the results of p value = 0.025